Application of SAW Method in Decision Support System for Determination of Exemplary Students - Fadila Shely Amalia; Debby Alita (Journal of Information Technology, Software Engineering and Computer Science, 2023)
The decision support system for determining exemplary students using the SAW method is a solution to existing problems so that the results of the assessment of exemplary students become more effective and efficient in terms of time and selection of exemplary students. Decision-making in the determination of exemplary students can be more detailed and more accurate from existing candidates to truly exemplary prospective students who meet the established criteria. This SAW method can help teachers in making decisions using weights that have been determined by the school. The results of the decision support system for determining exemplary students using the SAW method for Rank 1 were obtained by M. Pebi Ramadhan with a value of 0.992857. Rank 2 was obtained by Adittyo Yunanta with a value of 0.984286. Rank 3 was obtained by Aldo Al Farigi with a value of 0.982857.